ANALYSIS OF PROGRAMS FOR MECHATRONIC SYSTEMS MODELING - Vasylenko, O. V. (Radio Electronics, Computer Science, Control, 2015)
The problem of development of methodological support for simulation of mechatronic systems for structural and functional levels of abstraction has been solved. Object of study is the simulation process of mechatronic systems and automated control systems. The subject of the research are programs of engineering and computer-aided design of technical systems, universal mathematical processors (CAE, CAD and CAS-system, respectively). The purpose of the work is to improve the efficiency of decision-making process for engineers of electronics in selecting the best software and mathematical base for modeling of mechatronic systems. Mechatronic systems research revealed their features as multidomain objects and features in common – as subsystems of automated control, which are allow forming the main requirements for simulation programs. The analysis of mathematical base and software of CAE, CAD and CAS-systems and results of experiments on modeling and simulation at the causal and multi-domain approaches, made possible to determine the criteria for comparative analysis and to generate recommendations for choosing optimal modeling program for achieving the goals of study of mechatronic system. Based on the analysis of programs, the universal method of modeling and optimization of mechatronic systems in a cycle of computer-aided design has been developed.